Weight-related teasing in the school environment: associations with psychosocial health and weight control practices among adolescent boys and girls - Lampard, Amy; MacLehose, R.; Eisenberg, M.; Neumark-Sztainer, D.; Davison, K. (Springer New York LLC, 2014)
Weight-related teasing has been found to be associated with low self-esteem, depressive symptoms, body dissatisfaction, and weight control behaviors in adolescents. While research has typically examined weight-related teasing directed towards the individual, little is known about weight-related teasing at the school level. This study aimed to determine the association between the school-level prevalence of weight-related teasing and psychosocial factors, body dissatisfaction and weight control behaviors in adolescents. Adolescents (N = 2,793; 53.2 % female) attending 20 US public middle and high schools were surveyed as part of the Eating and Activity in Teens (EAT) 2010 study. Generalized estimating equations were used to estimate the association between school-level weight-related teasing and health variables, controlling for individual-level weight-related teasing, clustering of individuals within schools, and relevant covariates. A greater school-level prevalence of weight-related teasing was associated with lower self-esteem and greater body fat dissatisfaction in girls, and greater depressive symptoms in boys, over and above individual-level weight-related teasing.Dieting was associated with the school-level prevalence of weight-related teasing in analysis adjusted for covariates in girls, but not following adjustment for individual-level weight-related teasing. Unhealthy weight control behaviors, extreme weight control behaviors, and muscle-enhancing behaviors were not associated with the school-level prevalence of weight-related teasing in girls or boys. Findings from the current study, in conjunction with previous findings showing associations between weight-related teasing, psychological concerns, and weight control behaviors, highlight the importance of implementing strategies to decrease weight-related teasing in schools.